PENERAPAN KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HIRARC PADA PEKERJA INFORMAL DI PABRIK TAHU OEBUFU, KOTA KUPANG NUSA TENGGARA TIMUR - Banunu, Meosefan; Oga, Yoseph Petrus; Tokan, Maria Bengan; Mauguru, Selfianti Betriana; Ruli, Luh Putu; Roga, Anderias Umbu (Jurnal Abdi Insani, 2024)
K3 is something that cannot be separated in Human Resources (HR) and employment. This is so that occupational safety and health (K3) can have a positive impact on the sustainability of work productivity and not only improve social security and workers' welfare.Community Service (PKM) conducted on Workers at the Oebufu Tofu Factory, Oebufu Village, Oebobo District has The purpose of this service is to carry out K3 Hazard Risk Control using the HIRARC (Hazard Identification, Risk Assessment and Risk Control) method for Tofu Factory workers. In this service, we use the method of analysis of facts with the process of collecting data through interviews, field observations (during the tofu making process), documentation and directly examining the behavior at work by 16 Oebufu Tofu Factory workers. Work with a high level of risk was found at each stage of making tofu, namely the soybean soaking stage, the soybean peeling and washing stage, the soybean grinding stage, the soybean slurry boiling stage, the soybean slurry filtering stage, the solution application stage, the tofu printing stage and the tofu cutting stage, namely in the activity of lifting items with heavy loads such as buckets of soybeans and water, iron rulers, printing boards and so on which pose a risk of muscle soreness/ injury for workers at the Oebufu Tofu Factory.